Synthesis, Structural Analysis, and Theoretical Study of Amino Acid-Copper (II) Complexes via XRD and DFT - Al-Haidery, Nahed Hazim; Al-Hazam, Hanan Abduljaleel; Al-Saadawy, Nuha Hussain (Trends in Sciences, 2025)
New amino acid derivatives were synthesized to create copper (II) complexes, with the binding site influenced by pH levels. These complexes, derived from amino acids like alanine, histidine, tryptophan, and lysine, were characterized using various spectroscopic techniques, including IR, UV-Vis, and X-ray diffraction, which confirmed their expected crystal forms. Density functional theory (DFT) calculations were employed to analyze the electronic structures and stability of the complexes, revealing a correlation between the highest occupied molecular orbital (HOMO), lowest unoccupied molecular orbital (LUMO), energy gaps and their reactivity, thus aiding in the rational design of these compounds for applications in catalysis and biomimetic chemistry. HIGHLIGHTS New complexes were successfully prepared by reacting amino acids with terephthaloyl isothiocyanate (TPI). Study the reactivity of the isothiocyanate group (–N=C=S) of TPI with the amino (–NH₂) and carboxyl (–COOH) functional groups in amino acids. FT-IR: Confirm bond formation (e.g., C=O, C=S, N–H stretching vibrations) and peak shifts due to complexation. NMR (1H): Identify chemical shift changes indicative of coordination or hydrogen bonding. X-ray diffraction (XRD): Determine crystallinity or amorphous nature. Optimized geometry, HOMO-LUMO energies, and global reactivity descriptors (e.g., hardness, electrophilicity). GRAPHICAL ABSTRACT